Constrained Delaunay Triangulation for Ad Hoc Networks - Satyanarayana, D.; Rao, S. V. (Journal of Computer Systems, Networks, and Communications, 2008)
Geometric spanners can be used for efficient routingin wireless ad hoc networks. Computation of existing spannersfor ad hoc networks primarily focused on geometric propertieswithout considering network requirements. In this paper, wepropose a new spanner called constrained Delaunay triangulation(CDT) which considers both geometric properties and networkrequirements. The CDT is formed by introducing a small setof constraint edges into local Delaunay triangulation (LDel)to reduce the number of hops between nodes in the networkgraph. We have simulated the CDT using network simulator (ns-2.28) andcompared with Gabriel graph (GG), relative neighborhood graph(RNG), local Delaunay triangulation (LDel), and planarized localDelaunay triangulation (PLDel). The simulation results show thatthe minimum number of hops from source to destination is lessthan other spanners. We also observed the decrease in delay,jitter, and improvement in throughput.